Demonstration of a concentrated solar power and biomass plant for combined heat and power. (1st November 2022) - Jensen, Adam R.; Sifnaios, Ioannis; Perers, Bengt; Holst Rothmann, Jan; Mørch, Søren D.; Jensen, Poul V.; Dragsted, Janne; Furbo, Simon
Highlights: Hybridization of concentrated solar power and biomass combustion. Hydraulically connected solar collectors and biomass boilers. Annual efficiency of 93.6% due to use of waste heat for district heating. Sankey diagram illustrating the system energy flows. Split-cycle organic Rankine (ORC) with efficiency up to 22% Abstract: This study presents the design and performance of the Brønderslev hybrid plant – the world's first concentrated solar power (CSP)-biomass plant to utilize waste heat. The combined heat and power plant consist of a 16.6 MW parabolic trough collector field, two 10 MW biomass boilers, and an organic Rankine cycle (ORC) system with an electrical output of 4 MW. The solar collector field and biomass boilers are hydraulically connected and supply heat in parallel to the ORC system. A multi-stage heat recovery process ensures that the waste heat is supplied to the local district heating grid. The solar field can also be operated independently of the biomass plant, supplying heat directly to the district heating grid. The plant operation was investigated by analyzing measurements for 2020, and the monthly heat and electricity generation was calculated for each component. Additionally, the performance of the solar field and ORC was elucidated, and the ORC was found to have a maximum electrical efficiency of 20.6 %. Detailed results are shown for one day with joint heat supply to the ORC from the solar field and biomass boilers, and the corresponding energy flows are visualized using a Sankey diagram. The total efficiency of the biomass plant for the investigated year was 93.6 % based on the higher heating value of the fuel. Overall, it was found that the hybrid plant performed reliably and successfully demonstrated the potential of CSP-biomass hybridization.